2020
DOI: 10.3168/jds.2019-17934
|View full text |Cite
|
Sign up to set email alerts
|

Integrated gold superparticles into lateral flow immunoassays for the rapid and sensitive detection of Escherichia coli O157:H7 in milk

Abstract: Escherichia coli O157:H7 is a common harmful foodborne pathogen that can cause severe diseases at low infectious doses. Traditional lateral flow immunoassay (LFIA) for the rapid screening of E. coli O157:H7 in food suffers from low sensitivity due to its dependence on 20-to 40-nm gold nanoparticles (AuNP) with insufficient brightness as labels. To address this issue, we reported for the first time the successful synthesis of gold superparticles (GSP) by encapsulating numerous small AuNP into a polymer nanobead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…For example, Li et al synthesized a 342 nm gold superparticle by encapsulating oleylamine-AuNPs into polymer nanobeads. 34 The limit of detection (LOD) of gold superparticle-based LFSB for E. coli O157:H7 in milk was 5.95 × 10 2 colony forming units (CFU)/ mL, which was approximately 32-fold lower than that of a conventional 40 nm AuNP-based LFSB. Nanozymes with enzyme-like catalytic ability are widely used in bioassays to enhance colorimetric signals because they can catalyze the reaction of H 2 O 2 and chromogenic reagents such as 3,3′,5,5′tetramethylbenzidine (TMB).…”
Section: Lfsbs For Direct Detection Of Foodborne Pathogenic Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Li et al synthesized a 342 nm gold superparticle by encapsulating oleylamine-AuNPs into polymer nanobeads. 34 The limit of detection (LOD) of gold superparticle-based LFSB for E. coli O157:H7 in milk was 5.95 × 10 2 colony forming units (CFU)/ mL, which was approximately 32-fold lower than that of a conventional 40 nm AuNP-based LFSB. Nanozymes with enzyme-like catalytic ability are widely used in bioassays to enhance colorimetric signals because they can catalyze the reaction of H 2 O 2 and chromogenic reagents such as 3,3′,5,5′tetramethylbenzidine (TMB).…”
Section: Lfsbs For Direct Detection Of Foodborne Pathogenic Bacteriamentioning
confidence: 98%
“…To improve the detection sensitivity, many novel nanomaterials and signal amplification methods have been applied to antibody-based LFSBs. For example, Li et al synthesized a 342 nm gold superparticle by encapsulating oleylamine-AuNPs into polymer nanobeads . The limit of detection (LOD) of gold superparticle-based LFSB for E.…”
Section: Lfsbs For Direct Detection Of Foodborne Pathogenic Bacteriamentioning
confidence: 99%
“…The limit of detection was ∼5 × 10 5 cfu/ml for standard bacteria solutions. Li et al (2020) demonstrated the synthesized gold superparticles (GSP) by encapsulating numerous small AuNPs into a polymer nanobead using an evaporation‐induced self‐assembly method. The resultant GSP exhibited remarkably enhanced absorbance compared with the most widely used 40 nm AuNPs in LFIA.…”
Section: Recent Advances On E Coli O157:h7 Detection By Improved Lfiamentioning
confidence: 99%
“…Immunoassays are based on the specific binding between antibodies and antigens on the surface of target bacteria. [13][14][15] Enzyme-linked immunosorbent assay (ELISA) and colloidal gold immunochromatographic strip test (ICST) are accurate and highly specific. [16][17][18] Luciani et al developed a capture ELISA for the detection of Y. enterocolitica O:8 in food matrices.…”
Section: Introductionmentioning
confidence: 99%